The Effectiveness of Exercise Therapy in Reducing Pain, Joint Range of Motion and Functional Disability in Patients with Frozen Shoulder at Causa Primary Adhesive Capjualis: A Systematic Review: The Effectiveness of Exercise Therapy in Reducing Pain, Joint Range of Motion and Functional Disability in Patients with Frozen Shoulder at Causa Primary Adhesive Capjualis: A Systematic Review - Dwi Aprilia Sari; Wahyuni, Wahyuni (Indonesian Journal of Medicine, 2024)
Background: Adhesive capelusitis is a condition of inflammation, adhesions and shortening of the joint capsule resulting in significant limitations in joint movement from active and passive movements, thus disrupting human mobility and activities. The severity of Adhesive Capjualitis varies from mild to severe pain. The prevalence of Adhesive Capjualitis is 2%-5% of the entire population and occurs more often in women than men. Adhesive Capjualitis treatment has many options, namely conservative and surgical. Exercise therapy has many benefits for the body, providing exercise therapy for Adhesive Capjualitis can improve disability, prevent increasing severity and optimize health status and motor function. This study aims to review the effectiveness of exercise therapy in reducing pain, increasing joint range of motion and functional ability in patients with primary adhesive capelusitis. Subjects and Methods: A literature search was carried out using three databases PubMed, Google Scholar and PEdro which recorded studies on exercise therapy in patients with Frozen Shouldet at causa Primary Adhesive Capjualis in the period 2013-2023. PRISMA was used as a writing rule and methodological quality was checked with the PEDro scale. Results: Seventeen studies describing Exercise Therapy in Adhesive Caplaluis were included in this study, the methodology assessment using the PEDro scale was obtained with a score in the range of 4-10/10 with 2 articles being perfect, 11 articles being good, and 4 articles being adequate. Conclusion: Exercise therapy appears to be able to effectively reduce pain, increase range of motion and functional ability in primary Adhesive Capjualitis Keywords: Frozen Shoulder, Adhesive Capjualitis, Exercise Therapy, ROM, Functional Disability